Structural Basis of Ca2+-Dependent Self-Processing Activity of Repeat-in-Toxin Proteins - Kuban, Vojtech; Macek, Pavel; Hritz, Jozef; Nechvatalova, Katerina; Nedbalcova, Katerina; Faldyna, Martin; Sebo, Peter; Zidek, Lukas; Bumba, Ladislav (mBio, 2020)
The posttranslational Ca2+-dependent "clip-and-link" activity of large repeat-in-toxin (RTX) proteins starts by Ca2+-dependent structural rearrangement of a highly conserved self-processing module (SPM). Subsequently, an internal aspartate-proline (Asp-Pro) peptide bond at the N-terminal end of SPM breaks, and the liberated C-terminal aspartyl residue can react with a free ε-amino group of an adjacent lysine residue to form a new isopeptide bond. Here, we report a solution structure of the calcium-loaded SPM (Ca-SPM) derived from the FrpC protein of Neisseria meningitidis The Ca-SPM structure defines a unique protein architecture and provides structural insight into the autocatalytic cleavage of the Asp-Pro peptide bond through a "twisted-amide" activation. Furthermore, in-frame deletion of the SPM domain from the ApxIVA protein of Actinobacillus pleuropneumoniae attenuated the virulence of this porcine pathogen in a pig respiratory challenge model. We hypothesize that the Ca2+-dependent clip-and-link activity represents an unconventional strategy for Gram-negative pathogens to adhere to the host target cell surface.IMPORTANCE The Ca2+-dependent clip-and-link activity of large repeat-in-toxin (RTX) proteins is an exceptional posttranslational process in which an internal domain called a self-processing module (SPM) mediates Ca2+-dependent processing of a highly specific aspartate-proline (Asp-Pro) peptide bond and covalent linkage of the released aspartyl to an adjacent lysine residue through an isopeptide bond. Here, we report the solution structures of the Ca2+-loaded SPM (Ca-SPM) defining the mechanism of the autocatalytic cleavage of the Asp414-Pro415 peptide bond of the Neisseria meningitidis FrpC exoprotein. Moreover, deletion of the SPM domain in the ApxIVA protein, the FrpC homolog of Actinobacillus pleuropneumoniae, resulted in attenuation of virulence of the bacterium in a pig infection model, indicating that the Ca2+-dependent clip-and-link activity plays a role in the virulence of Gram-negative pathogens.
Keywords: Actinobacillus Infections; Protein Processing, Post-Translational; Bacterial Toxins; Bacterial Proteins; vápník; prasata; Virulence; Animals; Calcium; Actinobacillus pleuropneumoniae; bakteriální proteiny; bakteriální toxiny; zvířata; virulence; infekce bakteriemi rodu Actinobacillus; Swine; Membrane Proteins; membránové proteiny; Neisseria meningitidis; posttranslační úpravy proteinů